Assessment of the protective effects of pomegranate peel extract and n-acetyl cysteine alone or in combination with ornipural® against cadmium-induced bone toxicity in rat - Durmus Hatipoglu; İsmail Demircioglu; Kursat Filikci; Yasemin Korkmaz; Huseyin Gungor; Muhammed Demircioglu; Burak Dik (Eurasian Journal of Veterinary Sciences)
Aim: The present study was conducted to determine the effects of pomegranate peel extract (PPE) and N-acetyl Cysteine (NAC) alone or in their treatment combinations with commercial preparation Ornipural® (ORN) on bone metabolism against experimentally cadmium (Cd)-induced toxicity in rats. Materials and Methods: Totally 36 animals were used in the study including 6 Wistar Albino rats in each group. The animals were assigned to control, Cd, Cd+PPE, Cd+NAC, Cd+PPE+ORN and Cd+NAC+ORN groups. The animals in the groups were euthanized after their blood samples were taken at the end of the 8th week. The bones were subjected to maceration for morphometric and histopathological examinations after euthanasia. Results: The statistically significant differences were determined between the treatment groups and Cd group in terms of histopathological changes (osteoporotic alterations and changes in red bone marrow) and biomarkers (Ca, P and Mg) (P<0.05). Conclusion: Although PPE, NAC and treatment combinations with ORN applied against experimentally induced cadmium toxicity were determined to have positive effects on bone metabolism, it has been thought that carrying out trials by increasing treatment duration and dose would be beneficial to determine definite efficacy of the applied treatment protocols.